Arahan Lahan Insentif Pertanian Pangan Berkelanjutan Kabupaten Boyolali - Rizky Maulana; Samsul Ma'rif (Teknik PWK (Perencanaan Wilayah Kota), 2019)
Boyolali Regency is located on a strategic path, so that it can affect changes in activities around it. Agricultural land is vulnerable to being converted into built-up land. To be able to maintain agricultural land, it is necessary to direct the incentives for agricultural land. The direction of giving incentives is a reference for the government to provide incentives to agricultural landowners who maintain it. This is aimed at maintaining agricultural land from land conversion. When this is successful, food crop production will be maintained. So that it will create domestic food security. To achieve these results The method used in the preparation of the referral study of incentives for sustainable food agricultural land is to use descriptive analysis using a map to find out the distribution of land. Providing incentives on agricultural land in accordance with the land typology. Typology 1 receives the highest incentives while typology 4 receives the lowest incentives. Distribution of food cropland is quite evenly distributed, dominated by  typology 1 covering 9541.13 hectares (71.15%), followed by typology 2 covering 2230,005 hectares (16.62%), typology 3 covering 893.202 hectares (6, 66%), and typology 4 covers 746,022 hectares (5.57%). The provision of incentives is expected to maintain agricultural land to maintain food crop production in Boyolali District.